Optical Control of CD8+ T Cell Metabolism and Effector Functions - Amitrano, Andrea M.; Berry, Brandon J.; Lim, Kihong; Kim, Kyun-Do; Waugh, Richard E.; Wojtovich, Andrew P.; Kim, Minsoo (Frontiers in Immunology, 2021)
Although cancer immunotherapy is effective against hematological malignancies, it is less effective against solid tumors due in part to significant metabolic challenges present in the tumor microenvironment (TME), where infiltrated CD8+ T cells face fierce competition with cancer cells for limited nutrients. Strong metabolic suppression in the TME often leads to impaired T cell recruitment to the tumor site and hyporesponsive effector function via T cell exhaustion. Increasing evidence suggests that mitochondria play a key role in CD8+ T cell activation, effector function, and persistence in tumors. In this study, we showed that there was an increase in overall mitochondrial function, including mitochondrial mass and membrane potential, during both mouse and human CD8+ T cell activation. CD8+ T cell mitochondrial membrane potential was closely correlated with granzyme B and IFN-γ production, demonstrating the significance of mitochondria in effector T cell function. Additionally, activated CD8+ T cells that migrate on ICAM-1 and CXCL12 consumed significantly more oxygen than stationary CD8+ T cells. Inhibition of mitochondrial respiration decreased the velocity of CD8+ T cell migration, indicating the importance of mitochondrial metabolism in CD8+ T cell migration. Remote optical stimulation of CD8+ T cells that express our newly developed “OptoMito-On” successfully enhanced mitochondrial ATP production and improved overall CD8+ T cell migration and effector function. Our study provides new insight into the effect of the mitochondrial membrane potential on CD8+ T cell effector function and demonstrates the development of a novel optogenetic technique to remotely control T cell metabolism and effector function at the target tumor site with outstanding specificity and temporospatial resolution.